Reconstruction of Pleistocene Ice-Dammed Lake Outburst Floods in the Altai Mountains, Siberia 2005
DOI: 10.1130/0-8137-2386-8.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Pleistocene ice-dammed lake outburst floods in the Altai Mountains, Siberia

Abstract: In the Siberian Altai Mountains, where the sources of the River Ob are located, ice-dammed lake outburst fl oods, so-called jökulhlaups, occurred in Pleistocene times. Valley glaciers extended within the upper Chuja River catchment and dammed the river upstream of the village of Aktash, which generated ice-dammed lakes in the intramountainous Kuray and Chuja Basins. Indicated by shorelines and ice-rafted boulder deposits, the maximum lake level reached an altitude of 2100 m above sea level, which reveals a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(141 citation statements)
references
References 129 publications
(286 reference statements)
8
133
0
Order By: Relevance
“…In the Altai Mountains of Siberia, for example, floods 546 produced extensive deposits (Rudoy and Baker, 1993), including streamlined bars, but large erosional 547 streamlined forms are largely absent (Burr et al, 2009). This has been interpreted as due to the 548 channelization of floodwaters down previously incised river valleys (Herget, 2005) Our English Channel observations of streamlined islands also make interesting comparisons to those 557 described from Germany (Meinsen et al, 2011). This latter island population is found within 10 km of the 558 spill-point, and spread over a 50 km wide zone and surrounded by a network of channels.…”
mentioning
confidence: 65%
“…In the Altai Mountains of Siberia, for example, floods 546 produced extensive deposits (Rudoy and Baker, 1993), including streamlined bars, but large erosional 547 streamlined forms are largely absent (Burr et al, 2009). This has been interpreted as due to the 548 channelization of floodwaters down previously incised river valleys (Herget, 2005) Our English Channel observations of streamlined islands also make interesting comparisons to those 557 described from Germany (Meinsen et al, 2011). This latter island population is found within 10 km of the 558 spill-point, and spread over a 50 km wide zone and surrounded by a network of channels.…”
mentioning
confidence: 65%
“…The glacier dam-break flood in the Altai Mountains was one of the largest floods on the Earth [34]. The background of this megaflood was presented before [34][35][36].…”
Section: Megaflood Due To Glacier Dam-break Over Mobile Bedmentioning
confidence: 99%
“…The background of this megaflood was presented before [34][35][36]. This megaflood was modelled by Carling et al [36] using integrated 1D and 2D hydraulic models over a presumed fixed bed.…”
Section: Megaflood Due To Glacier Dam-break Over Mobile Bedmentioning
confidence: 99%
“…Based on terrestrial cosmogenic nuclide dates of moraines in the Chagan-Uzun valley, Gribenski et al (2016) suggested the Last Glacial Maximum in the SE Altai to be occurred about 17-19 ka. Associated with the glacial degradation final draining of ice-dammed lakes in the Chuya and Kurai intermountain depressions (Butvilovsky, 1993;Rudoy, 1995;Carling et al, 2002 andHerget, 2005) took place about 15.8 ± 1.8 ka, as it is evidenced by terrestrial cosmogenic nuclide dating (Reuther et al, 2006). The development of the Sartan ice-sheet glaciation within the framing ridges of the Chuya basin about 14 ka BP (Rudoy, 2005) does not confirmed by radiocarbon age of paleopeat in the Chikhachev range (Agatova et al, 2016).…”
Section: Regional Oroclimatic Features Controlling the Pleistocene Glmentioning
confidence: 99%
“…In contrast to Tuva, the effusive and tephra layers are absent in the sections of the Russian Altai. Repeated developing giant ice-dammed lakes in the region (Butvilovsky, 1993;Carling et al, 2002;Rudoy, 2005 andHerget, 2005) complicate utilizing terrestrial cosmogenic nuclide dating of ancient moraines within intermountain depressions. Besides the difficulties of applying the numerical dating techniques, in glacial sediments of Altai reference sections there is a lack of finds of macro-and microfauna (ostracods), and species composition does not allow establishing the glacial sequences.…”
Section: Introductionmentioning
confidence: 99%